Spectral properties of the Schrödinger operator with operator-valued potential - Mykytyuk, Ya. V.; Sushchyk, N. S. (Matematychni Studii, 2025)
Let $H$ be a separable Hilbert space, and let $\mathcal{H} := L_2(\mathbb{R}, H)$. In the space $\mathcal{H}$, we consider the self-adjoint Schrödinger operator of the form$T_q f = -f'' + qf,$where $q$ is a reflectionless operator-valued potential.Let $\mathcal{P}_+$ and $\mathcal{P}_-$ be the spectral projectors of the operator $T_q$ corresponding to the positive half-line $\mathbb{R}_+$ and the negative half-line $\mathbb{R}_-$, respectively. Define $\mathcal{H}_± := \mathcal{P}_± \mathcal{H}$, and let $T_q^± := T_q|_{\mathcal{H}_±}$.In this paper, we show that the operator $T_q$ has trivial kernel, and that the operator $T_q^+$ is unitarily equivalent to the unperturbed operator $T_0$. Next, let $B$ be an arbitrary bounded negative operator in a separable Hilbert space $H_1$ ($\dim H_1 \le \dim H$ if $\dim H < ∞$). Then we prove that there exists a reflectionless potential $q$ such that $T_q^-$ is unitarily equivalent to the operator $B$.A key role in this work is played by solutions of the operator Riccati equation of the form$S'(x) = K S(x) + S(x) K - 2 S(x) K S(x), \qquad x \in \mathbb{R},$where $K \in \mathcal{B}_+(H) \setminus \{0\}$, and $S\colon \mathbb{R} → \mathcal{B}(H)$. Here, $\mathcal{B}(H)$ is the Banach algebra of all bounded linear operators acting in $H$, and $\mathcal{B}_+(H) = \{A \in \mathcal{B}(H) \mid A ≥ 0\}$.